Perception and imagery of faces generate similar gender aftereffects. Issue 3 (15th March 2016) - Zamuner, Edoardo; Oxner, Matt; Hayward, William G.
ABSTRACT: Visual adaptation is known to bias perception away from the properties of the adapting stimuli, toward opposite properties, resulting in perceptual aftereffects. For example, prolonged exposure to a face has been shown to produce an identity aftereffect, biasing perception of a subsequent face toward the opposite identity. Such repulsive aftereffects have been observed for both visually perceived and visually imagined faces, suggesting that both perception and imagery yield typical aftereffects. However, recent studies have reported opposite patterns of aftereffects for perception and imagery of face gender. In these studies, visually perceived faces produced typical effects in which perception of androgynous faces was biased away from the gender of the adaptor, whereas imagery of the same stimuli produced atypical aftereffects, biasing the perceived gender of androgynous faces toward the gender of the adaptor. These findings are highly unusual and warrant further research. The present study aimed to gather new evidence on the direction of gender aftereffects following perception and imagery of faces. Experiment 1 had participants view and imagine female and male faces of famous and non-famous individuals. To determine the effect of concomitant visual stimulation on imagery and adaptation, participants visualized faces both in the presence and in the absence of a visual input. In Experiment 2, participants were adapted to perceived and imagined faces of famous and non-famous actors matched on gender typicality. This manipulation allowed us to determine the effect of face familiarity on the magnitude of gender aftereffects. Contrary to evidence from previous studies, our results demonstrated that both perception and imagery produced typical aftereffects, biasing the perceived gender of androgynous faces in the opposite direction to the gender of the adaptor. Famous faces yielded largest adaptation effects across tasks. Experiment 2 confirmed that these effects depended on familiarity rather than on sexual dimorphism. In both experiments, this effect was greater for perception than imagery. Additionally, imagery of famous faces produced strongest aftereffects when it was performed in the absence of visual stimulation. The implications of these findings are discussed.